2020
DOI: 10.3390/agronomy10020228
|View full text |Cite
|
Sign up to set email alerts
|

A Beetle in a Haystack: Are There Alternate Hosts of the Coffee Berry Borer (Hypothenemus hampei) in Puerto Rico?

Abstract: Can the coffee berry borer (Hypothenemus hampei, or CBB) use host plants other than coffee for food and shelter? The use of fruits other than coffee has been reported. However, the validity of these reports depends on accurate identification of CBB, which is sometimes uncertain. In this study we sampled potential alternate hosts in coffee farms in Puerto Rico. Fruits with perforations were collected and examined for the presence of scolytid beetles (Coleoptera: Curculionidae: Scolytinae). Scolytids were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…Shade coffee was also observed to harbor more natural enemies of CBB, including ants and entomopathogenic fungi [ 112 ]. While the use of other host plants has been reported in H. hampei [ 156 ], a recent study conducted in PR found that CBB rarely use fruits of alternate hosts, and did not feed or reproduce in these fruits [ 157 ].…”
Section: New Perspectives From Recent Invasions: Puerto Rico Hawamentioning
confidence: 99%
“…Shade coffee was also observed to harbor more natural enemies of CBB, including ants and entomopathogenic fungi [ 112 ]. While the use of other host plants has been reported in H. hampei [ 156 ], a recent study conducted in PR found that CBB rarely use fruits of alternate hosts, and did not feed or reproduce in these fruits [ 157 ].…”
Section: New Perspectives From Recent Invasions: Puerto Rico Hawamentioning
confidence: 99%
“…In both areas, old berries ("raisins") served as reservoirs for up to six months after the final harvest. In contrast, berries on the ground have been observed to decompose quickly under humid conditions in Puerto Rico, such that fallen berries may not serve as a major reservoir of the pest in this region [21,35]. Several studies have suggested that CBB can survive in alternate hosts (see Vega et al [35] for a review); however, these claims are difficult to evaluate because CBB may be confused with other species of small scolytid beetles.…”
Section: Cbb Infestation Damage and Economic Implicationsmentioning
confidence: 99%
“…In contrast, berries on the ground have been observed to decompose quickly under humid conditions in Puerto Rico, such that fallen berries may not serve as a major reservoir of the pest in this region [21,35]. Several studies have suggested that CBB can survive in alternate hosts (see Vega et al [35] for a review); however, these claims are difficult to evaluate because CBB may be confused with other species of small scolytid beetles. In Puerto Rico, scolytid beetles were collected from possible alternate hosts and identified by DNA barcoding [35].…”
Section: Cbb Infestation Damage and Economic Implicationsmentioning
confidence: 99%
“…;Vega et al 2020), dentro de la semilla, H. hampei pone los huevos Tabla 1. Detección de la broca del café y su registro en territorios y países productores de café en el mundo…”
unclassified